Motorizing fibres with geometric zero-energy modes - Baumann, Arthur; Sánchez-Ferrer, Antoni; Ziebert, Falko (Nature materials, 2018)
Active rotational motion of pre-strained materials is achieved by elastic deformations that break rotational symmetry around their axes.